The Analysis of Key Determinants in Zakat Performance: A Study from Stakeholders’ Perspective - Bedjo Santoso; Marno Nugroho (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Zakat is an important mechanism for the development of the country. Zakat contributes to social security and harmony to help bridge the gap and strengthen economic independence. Currently, zakat management managed by Zakat Management Organization is still largely managed informally, so some important things such as good governance, credibility, accountability, and professionalism have not been taken into account. The key to improving the quality and quantity of zakat as a productive and potential public fund is in its management. Professional zakat management is the main prerequisite that should not be abandoned. The purpose of this study is to analyze the degree of difference in perception and attributes of zakat management including trust, transparency, credibility, and accountability on the elements or parties in zakat performance namely zakat institutions, zakat collecting units, zakat payers and selected zakat recipients. The study used a questionnaire collection method with 150 respondents. The analysis is done by testing different perceptions. The results showed that the four stakeholders had different perceptions in terms of improving zakat management. Thus, further research is needed for the common perception of all parties involved in ZMO. The results of this study are expected to contribute to zakat performance research